Protecting the pawners: appraising the role of the Ministry of Housing and Local Authorities - Kassim, Salina; Hassan, Rusni; Abu Bakar, Elistina; Ilias, Ibtisam @ Ilyana (Canadian Center of Science and Education, 2019)
The role of consumer credit in modern society is vital particularly when poor economic conditions prevail and cost of living soars. It is prevalent that low and middle-income earners pledge their valuable in exchange for cash by resorting to pawnshops which are often labeled as a bank for poor. Being on the disadvantage side of having low bargaining power, the role of a regulator is indispensable. Therefore, this study examines the role of Ministry of Housing and Local Government which has been mandated to safeguard the interest of pawners under conventional pawnbroking transaction in Malaysia. The scope of discussion covers its institutional set-up, organisational structure while regulatory powers concentrate on licensing and enforcement based on the relevant statutory provisions. The discussion identifies several shortcomings in respect of licensing requirements, enforcement powers and human resources. Overall, the study finds that entrusting this ministry with consumer protection function is inappropriate. Recommendations to enhance protection for this class of consumer are proposed.